Fine-tuning the conjugate system of 0D heteroborane to construct an all-organic 0D/2D heterojunction for photocatalytic CO2 reduction. Issue 6 (December 2021) - Fu, Zhuquan; Huang, Hao; Song, Ting; Yin, Shiheng; Long, Bei; Ali, Atif; Deng, Guo-Jun
Abstract: The 0D/2D composite is considered a potential material due to its size tunability, thereby enhancing the separation efficiency of photoinduced carrier. Herein, a 0D/2D composite of heteroborane (xBC) confined in porous g-C3 N4 nanosheets (PCN) was prepared by a facile synthesis strategy. The xBC complex is loaded on the surface of PCN sample to make the interface tight and shorten the charge diffusion distance, which can obviously promote the separation of photoinduced carriers. Moreover, through the use of organic synthesis strategies, the molecular structure of xBC is regulated at quantum size, thereby significantly affecting the ability of boron atoms to activate CO2 molecule. The reduction products of 2BCN composite are CH4, CO and H2, which is 10.2, 23.9 and 36.4 folds than that of PCN, respectively. This work provides insights for reimplanting active sites in quantum dots to further achieve robust solar CO2 conversion. Graphical Abstract: ga1 Highlights: An all-organic 0D/2D heteroborane/porous g-C3 N4 was prepared through a facile synthesis strategy. The 0D/2D composite makes the interface tight and shorten the charge diffusion distance. The molecular structure of xBC is regulated at quantum size to affect the ability of activate CO2 . 2BCN sample exhibits excellent photocatalytic performance.